Factors Related To The Event Of Diarrhea In Todllers Aged 1-3 Years In Doyo Lama Village, Waibu District, Jayapura Regency - Kismiyati Kismiyati; Nasrah Nasrah; Theresia Febriana Christi Tyas Utami (Science Midwifery, 2022)
Diarrhea is still one of the main public health problems in Indonesia. The incidence of diarrhea in Jayapura Regency in 2017 increased by 4,265 cases and in 2018 with 4,984 cases (4.49%) treated Objective: To determine the risk factors associated with the incidence of diarrhea in toddlers aged 1-3 years in Doyo Lama Village, Waibu District, Jayapura Regency. Research Methods : Analytical descriptive research using cross sectional design Results and Discussion : There is a relationship between hand washing habits (p=0.000), environmental status (p=0.000) with the incidence of diarrhea and giving MP-ASI (p=0,360), respondents' income, is not related to the incidence of diarrhea with the value of the Kruskal Wallis P test result of (p= 0.2480) in toddlers aged 1-3 in Doyo Lama Village, Waibu District, Jayapura Regency. Conclusions and Suggestions : To mothers who have toddlers to pay more attention to the use of clean water, get used to washing hands with soap and running water, give MP-ASI on time, and maintain a clean environment that meets health requirements.